Batteries incorporating silica fibers
By using silica fibers and powder as structural matrix of the battery, poor reliability and material problems of flexible batteries in the prior art are solved, and efficient charge storage and environmentally friendly battery manufacturing are achieved.
Patent Information
- Application Number
- CN201980042045.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-05-25
- Filing Date
- 2019-05-24
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2039-05-24
AI Technical Summary
Existing battery technology has problems with poor reliability, low charging-storage capacity or low charging/discharge rates in flexible batteries, while relying on expensive and toxic foreign materials.
Silica fibers and/or the powder thus formed are used as structural substrates for batteries or other charge storage devices, and electrochemical charge storage and conductivity are achieved by mixing, applying or incorporating with other materials.
It achieves more environmentally friendly battery manufacturing, meets the requirements of next-generation electronic devices, and improves charge storage capacity, temperature stability and cycle life.
Smart Images

Figure CN112335075B_ABST
Abstract
Description
[0001] Related Applications
[0002] This application claims the benefit of and priority to U.S. Provisional Patent Application No. 62 / 676,435, filed May 25, 2018, the entire disclosure of which is incorporated herein by reference. Technical Field
[0003] In various embodiments, the present invention is directed to charge storage devices incorporating silica fibers. Background Art
[0004] Batteries have been used for electrochemical energy storage for hundreds of years, and they have become increasingly ubiquitous, especially as microelectronics miniaturization has enabled widespread adoption of many different types of consumer electronic devices. As next-generation electronic devices become increasingly lightweight and even more flexible, the demand for battery technology will only increase. Various technologies for flexible batteries have been proposed, but implementation of such technologies has been hampered by poor reliability, low charge-storage capacity, or low charge / discharge rates. In addition, various battery technologies are based on exotic and expensive materials that are often toxic, creating another barrier to adoption.
[0005] In contrast, silicon dioxide, or silica, is one of the most abundant materials on Earth and is the primary component of most types of sand. Silica has a variety of favorable properties that make it useful in many different industries and products. For example, the high electrical resistance of silica enables its use as a high-performance insulator in microelectronic devices, such as as a gate dielectric material in field effect transistors. Silica is also used to produce glass that can be used in many different applications. For example, optical fibers are made using silica and have enabled the formation and development of global optical communications networks. Silica has also been used on a microscopic scale, as silica particles have been used as abrasives, desiccants, and to form molds for investment casting of metallic materials. However, silica has not yet been used as a material for batteries and other charge storage devices (e.g., supercapacitors). The use of silica may enable the manufacture and use of batteries that are more environmentally friendly and can be used to meet the requirements of next-generation electronic devices. Summary of the invention
[0006] According to various embodiments of the present invention, silica fibers and / or powders formed therefrom are used as structural matrices for various components of batteries or other charge storage devices. Various components of the battery incorporate other materials mixed with, applied to, and / or incorporated into the silica fibers to achieve electrochemical charge storage and conductivity of the battery. The silica fibers themselves can be made of a colloidal material that is electrospun to form a fiber mat. The mat itself (or a portion thereof) can be used in a battery with or without additional processing (e.g., pressing and / or incorporating additive materials). In various embodiments, the mat is fragmented into a powder or dust that may include fiber fragments, consist essentially of, or consist of. Powders that may have been incorporated with one or more additive materials introduced before, during, or after the fiber electrospinning process can be used in one or more regions of the battery. In various embodiments, the powder is mixed with one or more additives for use in one or more battery regions. In other embodiments, the powder is pressed into a planar sheet and used in a battery with or without incorporating one or more additives.
[0007] In various embodiments, silica fibers can be prepared by electrospinning sol-gels, which can be prepared with a silane oxide reagent such as tetraethyl orthosilicate (TEOS), an alcohol solvent, and an acid catalyst. In various embodiments, the sol-gel is produced by ripening the sol under controlled environmental conditions, and / or monitoring the properties of the sol or sol-gel during the ripening process in order to determine various processing windows during which electrospinning of the sol-gel can be successfully performed. As known in the art, a "sol" is a colloidal solution that gradually evolves toward the formation of a "gel" (i.e., a two-phase system that includes both a liquid phase and a solid phase). In this article, the term "sol-gel" is used to refer to a gel that can be electrospun into fibers or fiber mats produced by a sol-gel process.
[0008] In various embodiments, the controlled environment for ripening the sol may involve controlled conditions in terms of humidity, temperature, and optional atmospheric pressure. For example, the humidity may be controlled within a range of about 30% to about 90%, and the temperature may be controlled within a range of about 50°F to about 90°F. By controlling the environmental conditions during ripening, the gel may be electrospun during the time when spinning is optimal, and if the ripening process is accelerated by direct heating, electrospinning may occur within a very small window of only a few minutes. When the sol is ripened at a constant humidity in the range of about 50% to 80% and a temperature of about 60°F to 80°F, the sol will ripen (gel) within a few days, and the window for successful electrospinning may be extended to at least a few hours, and in some embodiments to a few days. Therefore, the sol may be ripened in a housing that may include one or more environmental monitors such as a temperature reading device and / or a humidity reading device. In addition, the relative weight of the gas and / or sol generated or released by the sol during the ripening process may be monitored to determine the appropriate or optimal time for electrospinning.
[0009] Once the sol is fully matured into a sol-gel, it is electrospun to form a tangled silica fiber mat. Once electrospun, the silica fibers can have variable diameters, such as in the range of about 50nm to 5μm. In some embodiments, the fibers are primarily in the range of about 100nm to about 2μm, or primarily in the range of about 200nm to about 1000nm. In order to manufacture various regions of the battery, different materials can be applied to the silica fibers during and / or after the electrospinning process so that the resulting fibers, fiber mats or powders have different properties. For example, carbon additives such as graphene, amorphous carbon and / or graphite can be applied to the sol-gel and / or the silica fibers after or during electrospinning; such fibers can be used for battery anodes and / or fragmented into powders for use in battery anodes. Similarly, a lithium additive (e.g., a lithium metal oxide (e.g., a lithium transition metal oxide such as lithium cobalt oxide or lithium manganese oxide) or a lithium metal phosphate (e.g., lithium iron phosphate) can be applied to the sol-gel and / or electrospun silica fibers after or during electrospinning; such fibers can be used in battery cathodes and / or fragmented into powders for use in battery cathodes. Exemplary lithium additives according to embodiments of the present invention include lithium metal oxides such as lithium cobalt oxide, and / or lithium manganese oxide, and / or lithium metal phosphates such as lithium iron phosphate. In various embodiments, the lithium additive includes, consists essentially of, or consists of lithium metal oxide salts such as LiNiMnCoO2 (NMC), LiNiCoAlO2 (NCA), LiCoO2 (LCO), LiFePO4 (LFP), and the like.
[0010] In various embodiments, additives such as carbon additives and / or lithium additives may be incorporated into (e.g., mixed with) the powder formed by fragmentation of the electrospun fibers. In various embodiments, the anode region may include, consist essentially of, or consist of a powder of silica fibers mixed with (e.g., as a balance) carbon additives, for example, at about 0.5% to about 90% (or about 0.5% to about 50%, or about 0.5% to about 10%) by weight or volume. In various embodiments, the cathode region may include, consist essentially of, or consist of a powder of silica fibers mixed with (e.g., as a balance) lithium additives, for example, at about 0.5% to about 90% (or about 0.5% to about 50%, or about 0.5% to about 10%) by weight or volume. The cathode region according to embodiments of the present invention may also incorporate carbon additives, such as amorphous carbon and / or graphitic carbon.
[0011] Batteries according to embodiments of the present invention may also incorporate a separator layer that (1) prevents or substantially prevents physical contact between the anode region and the cathode region, and (2) incorporates an electrolyte that enables charge to be transferred between the anode region and the cathode region through the separator. In various embodiments, the separator incorporates an electrolyte, such as a mixture of an organic solvent (e.g., ethylene, dimethyl / ethyl carbonate, and / or N-methyl-2-pyrrolidone) and one or more lithium salts, such as lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate monohydrate (LiAsF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), or lithium trifluoromethanesulfonate (LiCF3SO3). In various embodiments, the separator includes, consists essentially of, or consists of a polymer layer that is typically porous to enable charge transfer (e.g., by the flow of ionic charge carriers). For example, the size of the pores in the polymer layer may range from about 5 nm to about 100 nm. Such polymeric layers may comprise, consist essentially of, or consist of, for example, one or more polymeric materials such as polyethylene, polypropylene, polytetrafluoroethylene, polyvinyl chloride, and / or polymer blends comprising one or more of these, with or without one or more other polymeric materials.
[0012] In various embodiments, the separator layer may additionally incorporate one or more silica fiber sheets. As used herein, a "sheet" of silica fibers refers to an electrospun mat of silica fibers with or without additional pressing or processing, or to a pressed layer of a powder (e.g., fiber fragments) formed by fragmentation of an electrospun silica fiber mat. For example, a first silica fiber sheet may be disposed between (and, e.g., in direct mechanical contact with) a polymer layer and an anode region, and / or a second silica fiber sheet may be disposed between (and, e.g., in direct mechanical contact with) a polymer layer and a cathode region. In various embodiments, incorporating one or more silica fiber sheets protects the polymer layer from thermal decomposition and / or deformation, enhances the mechanical integrity of the battery's internal structure, and / or improves ion mobility within the battery.
[0013] In various embodiments, such as those incorporating one or more silica fiber sheets as part of a separator, the cell can be substantially free of silica fibers and / or silica fiber powder in the anode region and / or the cathode region. In various embodiments, the cell can incorporate silica fibers and / or silica fiber powder in the anode region, the cathode region, or both.
[0014] Various embodiments of the present invention include cells incorporating multiple anode-separator-cathode stacks electrically connected in series or in parallel with each other; such cells may exhibit increased charge storage capabilities. As used herein, an additive material (e.g., a carbon additive and / or a lithium additive) such as one of the various materials listed above and herein is "incorporated" into or on a region (e.g., in or on silica fibers and / or silica fiber powder) of a cell in which the additive material is "incorporated" into or on that region, the additive material may be bonded or otherwise adhered to the fibers or powder particles in a substantially solid form, present within the crystal structure of the fibers or powder particles themselves, and / or present as a solid or liquid form (e.g., with a liquid binder or carrier such as an organic liquid such as propylene carbonate and / or other organic polymers mentioned herein) within a mat or sheet (e.g., within the pores or spaces between fibers) or within a collection of powder particles.
[0015] Various battery regions (e.g., cathode regions, anode regions, and / or electrolyte / separator regions) according to embodiments of the present invention may include a binder material (e.g., polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), etc.) and / or a solvent (e.g., any of the organic liquids N-methyl-2-pyrrolidone (NMP), ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), etc. disclosed herein). Such materials may be used when manufacturing various battery regions (e.g., cathode regions and / or anode regions) (e.g., to form a uniform slurry of the desired material), and such materials may be substantially removed before or during the final assembly of the battery. Thus, only trace or unintentional amounts of binder and / or solvent may remain in one or more regions of the battery. In various embodiments, the anode region and / or cathode region may include one or more metal solid regions (e.g., metal sheets or foils) that may help ensure electrical contact between the anode region and / or cathode region of the battery and an electrode (e.g., a portion of the housing). For example, the anode region and / or the cathode region may include a substrate layer comprising, consisting essentially of, or consisting of one or more metal sheets or foils, which may include, consisting essentially of, or consisting of, for example, copper and / or aluminum.
[0016] Batteries according to embodiments of the present invention may have any of a variety of shapes and sizes. For example, batteries according to embodiments of the present invention may have a form factor of commercially available batteries such as "coin cells" (e.g., LIR 2032, etc.), button cells (e.g., 1220, 1254, 1632, 2050, 2477, etc.) or cylindrical batteries (e.g., 14430-18650, AA, AAA, etc.). Batteries according to embodiments of the present invention may be cylindrical and may have a range of different sizes. For example, the diameter of a battery according to an embodiment of the present invention may be in the range of about 10 mm to about 50 mm. The height of a battery according to an embodiment of the present invention may be in the range of about 2 mm to about 100 mm. Batteries according to embodiments of the present invention may have a size (e.g., diameter and / or height) greater than the sizes listed above.
[0017] Compared to conventional batteries, batteries according to embodiments of the present invention have one or more of the following advantages: improved ion mobility (due to, for example, greater porosity), higher charge density, greater temperature stability (e.g., structural stability and / or charge / discharge rate variations at extreme temperatures (e.g., exceeding -20°C and / or 45°C)), improved utilization of active materials (e.g., cathode and / or anode materials) for equivalent performance levels, improved reversible capacity, and longer shelf life. For example, coin-type batteries according to embodiments of the present invention (e.g., batteries incorporating LiCoO2 in the cathode) may have a nominal voltage ranging from about 3 V to about 4 V (e.g., about 3.7 V), a maximum capacity greater than 40 mAh, a volumetric energy density greater than 149 Wh / L, a specific energy greater than 56 Wh / kg, a constant charge current and / or maximum continuous discharge current greater than 0.04 A, a self-discharge rate less than 1% / year, and / or a cycle life of greater than 500 cycles at 0.2 C mA discharge. In other examples, cylindrical batteries according to embodiments of the present invention (e.g., batteries incorporating LiNiMnCoO2 in the cathode) may have a nominal voltage ranging from about 3 V to about 4 V (e.g., about 3.7 V), a maximum capacity greater than 3500 mAh, a volumetric energy density greater than 738 Wh / L, a specific energy greater than 261 Wh / kg, a constant charge current greater than 1.7 A, a maximum continuous discharge current greater than 10 A, a self-discharge rate less than 1% / year, and / or a cycle life greater than 300-500 cycles at 0.2 C mA discharge.
[0018] Various embodiments of the present invention have advantageous properties when used as batteries and other charge storage devices. For example, the silica fiber sheets and / or silica fiber powders will limit the thermal expansion of various additives (e.g., lithium additives) used in various embodiments. Lithium has a large coefficient of thermal expansion, which can cause reliability issues during operation of conventional lithium-ion batteries as the temperature of lithium-containing regions increases and decreases. The silica fiber-based structures (e.g., sheets and / or powders) of batteries according to embodiments of the present invention provide sufficient porosity to accommodate thermal cycling of additive-containing layers without significant deformation of the battery itself.
[0019] Furthermore, the silica fiber-based structures used in various regions or structures of the battery according to embodiments of the present invention have a large surface area (e.g., in the range of about 50 m 2 / g to about 100m 2 / gram, or even greater), thereby achieving a large charge storage capacity. The silica fiber-based structure is also advantageously thermally insulating and thus thermally isolates various areas of the battery from extreme environmental conditions, thereby increasing the life of the battery.
[0020] Batteries according to embodiments of the present invention may be used in any of a variety of different applications, for example, consumer applications (such as personal electronics, centralized electrical energy storage units for portable devices, power supply units) as well as military and space applications.
[0021] In various embodiments of the present invention, one or more regions of the battery include, consist essentially of, or consist of a silica fiber powder (with or without additives). For example, in various embodiments, once the silica fiber mat is successfully electrospun, it can be processed into a powder or dust. For example, the electrospun mat can be "fragmented", i.e., broken, cut, ground, milled (e.g., in a ball mill or other milling device), pulverized or otherwise divided into small fragments that retain the fiber structure. As used herein, the term "fiber fragment" (or "fiber mat fragment", or simply "fragment") refers to a small particle, part or flake of a fiber mat having an average size that is greater than (e.g., 5×, 10×, or even 100×) the width of at least some of the fibers of the mat. In various embodiments, the average size of the fiber fragments ranges from about 20 μm to about 200 μm. The fiber fragments can therefore resemble a microscopic scale version of the electrospun mat itself, such as an interwoven collection of silica fibers, and are therefore generally porous and have a low density. Thus, fiber fragments can be contrasted with other types of micron-sized particles, such as the substantially spherical particles used in colloidal silica, each of which is a single, individual unit or particle, rather than a collection of small fibers. Various portions (e.g., edges) of the fiber fragments can have sharp and / or broken edges resulting from the fragmentation process used to form the fragments from the electrospun mat. As used herein, the terms "silica fiber powder," "silica powder," "silica dust," and "fiber dust" include a collection of particles produced by fragmentation of electrospun fiber mats and / or fibers, and can include fiber fragments and / or other powder particles resulting from such fragmentation.
[0022] Embodiments of the present invention may employ silica fibers, fragments thereof and / or mixtures incorporating such fibers or fragments, and / or methods for making such fibers or fragments as described in detail in U.S. patent application serial number 15 / 934,599 filed on March 23, 2018 (published as U.S. Patent No. 10,111,783), U.S. patent application serial number 16 / 131,531 filed on September 14, 2018, U.S. patent application serial number 16 / 353,181 filed on March 14, 2019, and U.S. patent application serial number 16 / 367,313 filed on March 28, 2019, the entire disclosure of each of which is incorporated herein by reference.
[0023] In one aspect, embodiments of the invention feature a charge storage device that includes, consists essentially of, or consists of an anode region, a cathode region, and a separator disposed between the anode region and the cathode region. The anode region includes, consists essentially of, or consists of a first silica fiber powder and a carbon additive. The cathode region includes, consists essentially of, or consists of a second silica fiber powder and a lithium additive. The separator includes an electrolyte material.
[0024] Embodiments of the invention may include one or more of the following in any combination in various combinations. The carbon additive may include, consist essentially of, or consist of graphene, amorphous carbon, and / or graphite. The lithium additive may include, consist essentially of, or consist of lithium metal oxide and / or lithium metal phosphate. The electrolyte material may include, consist essentially of, or consist of an organic solvent and a lithium salt. The electrolyte material may include, consist essentially of, or consist of a lithium salt.
[0025] The separator may include (i) one or more silica fiber sheets, and (ii) a polymer layer, consisting essentially of or consisting of. The separator may include (i) a first silica fiber sheet, (ii) a second silica fiber sheet, and (iii) a polymer layer disposed between the first silica fiber sheet and the second silica fiber sheet, consisting essentially of or consisting of. The one or more silica fiber sheets may be formed at least in part by electrospinning a sol-gel. The sol-gel may be prepared using tetraethyl orthosilicate (TEOS). Prior to electrospinning the sol-gel, the sol-gel may be produced from an initial sol comprising, consisting essentially of or consisting of, 70 wt % to 90 wt % TEOS, 8 wt % to 25 wt % ethanol, an acid catalyst, and water. The initial sol may comprise, consisting essentially of or consisting of, 70 wt % to 90 wt % TEOS, 8 wt % to 25 wt % ethanol, an acid catalyst, and water. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and a balance of water. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water, and is essentially composed of or consisting of. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water, and is essentially composed of or consisting of. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water, and is essentially composed of or consisting of. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water, and is essentially composed of or consisting of. The initial sol may comprise, consist essentially of, or consist of 75 to 85 wt % TEOS, 12 to 20 wt % ethanol, and about 2 to 5 wt % water. The initial sol may comprise, consist essentially of, or consist of about 80 wt % TEOS, about 17 wt % ethanol, and about 3 wt % water. The acid catalyst may comprise, consist essentially of, or consist of HCl. The initial sol may comprise less than about 0.1 wt % acid catalyst. The initial sol may comprise 0.02 to 0.08 wt % acid catalyst. The initial sol may comprise one or more reagents that change one or more properties of the initial sol, sol-gel, and / or silica fiber.
[0026] Producing sol-gel may include transforming the initial sol for at least 2 days under conditions where humidity is in the range of about 40% to about 80% and temperature is in the range of 50°F to 90°F. The initial sol may be allowed to transform for at least 3 days, at least 4 days, at least 5 days, at least 6 days, or at least 7 days. The initial sol may be allowed to transform for 2 to 10 days, and in some embodiments, for 2 to 7 days. When the weight is 20% to 40% of the initial weight of the initial sol or sol-gel before maturation (transformation), the sol-gel may be electrospun. When the generation of ethylene vapor is 10% to 20% of the peak generation of ethylene vapor during the maturation (transformation) of the initial sol or sol-gel before maturation, the sol-gel may be electrospun. When the ethylene vapor generated by the sol-gel is 10% to 40% relative to the initial sol or sol-gel before maturation (transformation), the sol-gel may be electrospun.
[0027] The first silica fiber powder may be formed by a process comprising, consisting essentially of, or consisting of the following steps: (i) electrospinning a sol-gel to form a silica fiber mat, and (ii) fragmenting the mat to form a silica fiber powder. The silica fiber powder may include, consist essentially of, or consist of particles and / or fiber fragments that may have an average size (e.g., average diameter, length, width, or other dimension) in the range of about 20 μm to about 200 μm. The silica fiber powder may include, consist essentially of, or consist of a plurality of fiber fragments, each of which is composed of a plurality of silica fibers or portions thereof. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 50 nm to about 5 μm. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 200 nm to about 1000 nm. The silica fiber powder may consist essentially of or consist of SiO2.
[0028] Sol-gel can be prepared with tetraethyl orthosilicate (TEOS). Before electrospinning sol-gel, sol-gel can be produced by an initial sol, which comprises, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst. The initial sol may comprise, and consist essentially of or consist of, 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water. The initial sol may comprise, and consist essentially of or consist of, about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water. The acid catalyst may comprise, and consist essentially of or consist of, HCl. The initial sol may comprise an acid catalyst less than about 0.1% by weight. The initial sol may comprise an acid catalyst of 0.02% to 0.08% by weight. The initial sol may contain one or more agents that alter one or more properties of the initial sol, the sol-gel, and / or the silica fibers.
[0029] The process of forming the first silica fiber powder may include incorporating a carbon additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat includes the carbon additive incorporated therein. The process of forming the first silica fiber powder may include incorporating the carbon additive onto the silica fibers during electrospinning of the silica fibers. The process of forming the first silica fiber powder may include incorporating the carbon additive onto the silica fiber mat prior to fragmentation of the silica fiber mat. The process of forming the first silica fiber powder may include incorporating the carbon additive onto the silica fiber powder after fragmentation of the silica fiber mat.
[0030] The second silica fiber powder may be formed by a process comprising, consisting essentially of, or consisting of the following steps: (i) electrospinning a sol-gel to form a silica fiber mat, and (ii) fragmenting the mat to form a silica fiber powder. The silica fiber powder may include, consist essentially of, or consist of particles and / or fiber fragments that may have an average size (e.g., average diameter, length, width, or other size) in the range of about 20 μm to about 200 μm. The silica fiber powder may include, consist essentially of, or consist of a plurality of fiber fragments, each of which is composed of a plurality of silica fibers or portions thereof. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 50 nm to about 5 μm. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 200 nm to about 1000 nm. The silica fiber powder may consist essentially of or consist of SiO2.
[0031] Sol-gel can be prepared with tetraethyl orthosilicate (TEOS). Before electrospinning sol-gel, sol-gel can be produced by an initial sol, which comprises, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst. The initial sol may comprise, and consist essentially of or consist of, 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water. The initial sol may comprise, and consist essentially of or consist of, about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water. The acid catalyst may comprise, and consist essentially of or consist of, HCl. The initial sol may comprise an acid catalyst less than about 0.1% by weight. The initial sol may comprise an acid catalyst of 0.02% to 0.08% by weight. The initial sol may contain one or more agents that alter one or more properties of the initial sol, the sol-gel, and / or the silica fibers.
[0032] The process of forming the second silica fiber powder may include incorporating a lithium additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat includes the lithium additive incorporated therein. The process of forming the second silica fiber powder may include incorporating the lithium additive onto the silica fibers during electrospinning of the silica fibers. The process of forming the second silica fiber powder may include incorporating the lithium additive onto the silica fiber mat prior to fragmentation of the silica fiber mat. The process of forming the second silica fiber powder may include incorporating the lithium additive onto the silica fiber powder after fragmentation of the silica fiber mat.
[0033] In another aspect, embodiments of the invention feature a method of making a charge storage device. An anode region is formed. A cathode region is formed. A separator is disposed between the anode region and the cathode region. The anode region includes, consists essentially of, or consists of a first silica fiber powder and a carbon additive. The cathode region includes, consists essentially of, or consists of a second silica fiber powder and a lithium additive. The separator includes an electrolyte material.
[0034] Embodiments of the invention may include one or more of the following in any combination in various combinations. The carbon additive may include, consist essentially of, or consist of graphene, amorphous carbon, and / or graphite. The lithium additive may include, consist essentially of, or consist of lithium metal oxide and / or lithium metal phosphate. The electrolyte material may include, consist essentially of, or consist of an organic solvent and a lithium salt. The electrolyte material may include, consist essentially of, or consist of a lithium salt.
[0035] The separator may include (i) one or more silica fiber sheets, and (ii) a polymer layer, consisting essentially of or consisting of. The separator may include (i) a first silica fiber sheet, (ii) a second silica fiber sheet, and (iii) a polymer layer disposed between the first silica fiber sheet and the second silica fiber sheet, consisting essentially of or consisting of. The one or more silica fiber sheets may be formed at least in part by electrospinning a sol-gel. The sol-gel may be prepared using tetraethyl orthosilicate (TEOS). Prior to electrospinning the sol-gel, the sol-gel may be produced from an initial sol comprising, consisting essentially of or consisting of, 70 wt % to 90 wt % TEOS, 8 wt % to 25 wt % ethanol, an acid catalyst, and water. The initial sol may comprise, consisting essentially of or consisting of, 70 wt % to 90 wt % TEOS, 8 wt % to 25 wt % ethanol, an acid catalyst, and water. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and a balance of water. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water, and is essentially composed of or consisting of. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water, and is essentially composed of or consisting of. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water, and is essentially composed of or consisting of. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water, and is essentially composed of or consisting of. The initial sol may comprise, consist essentially of, or consist of 75 to 85 wt % TEOS, 12 to 20 wt % ethanol, and about 2 to 5 wt % water. The initial sol may comprise, consist essentially of, or consist of about 80 wt % TEOS, about 17 wt % ethanol, and about 3 wt % water. The acid catalyst may comprise, consist essentially of, or consist of HCl. The initial sol may comprise less than about 0.1 wt % acid catalyst. The initial sol may comprise 0.02 to 0.08 wt % acid catalyst. The initial sol may comprise one or more reagents that change one or more properties of the initial sol, sol-gel, and / or silica fiber.
[0036] Producing sol-gel may include transforming the initial sol for at least 2 days under conditions where humidity is in the range of about 40% to about 80% and temperature is in the range of 50°F to 90°F. The initial sol may be allowed to transform for at least 3 days, at least 4 days, at least 5 days, at least 6 days, or at least 7 days. The initial sol may be allowed to transform for 2 to 10 days, and in some embodiments, for 2 to 7 days. When the weight is 20% to 40% of the initial weight of the initial sol or sol-gel before maturation (transformation), the sol-gel may be electrospun. When the generation of ethylene vapor is 10% to 20% of the peak generation of ethylene vapor during the maturation (transformation) of the initial sol or sol-gel before maturation, the sol-gel may be electrospun. When the ethylene vapor generated by the sol-gel is 10% to 40% relative to the initial sol or sol-gel before maturation (transformation), the sol-gel may be electrospun.
[0037] Forming the anode region may include, consist essentially of, or consist of the following steps: (i) electrospinning a sol-gel to form a silica fiber mat, and (ii) fragmenting the mat to form a silica fiber powder. The silica fiber powder may include, consist essentially of, or consist of particles and / or fiber fragments that may have an average size (e.g., average diameter, length, width, or other size) in the range of about 20 μm to about 200 μm. The silica fiber powder may include, consist essentially of, or consist of a plurality of fiber fragments, each of which is composed of a plurality of silica fibers or portions thereof. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 50 nm to about 5 μm. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 200 nm to about 1000 nm. The silica fiber powder may consist essentially of or consist of SiO2.
[0038] Sol-gel can be prepared with tetraethyl orthosilicate (TEOS). Before electrospinning sol-gel, sol-gel can be produced by an initial sol, which comprises, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst. The initial sol may comprise, and consist essentially of or consist of, 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water. The initial sol may comprise, and consist essentially of or consist of, about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water. The acid catalyst may comprise, and consist essentially of or consist of, HCl. The initial sol may comprise an acid catalyst less than about 0.1% by weight. The initial sol may comprise an acid catalyst of 0.02% to 0.08% by weight. The initial sol may contain one or more agents that alter one or more properties of the initial sol, the sol-gel, and / or the silica fibers.
[0039] Forming the anodic region may include incorporating the carbon additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat includes the carbon additive incorporated therein. Forming the anodic region may include incorporating the carbon additive onto the silica fibers during electrospinning of the silica fibers. Forming the anodic region may include incorporating the carbon additive onto the silica fiber mat prior to fragmentation of the silica fiber mat. Forming the anodic region may include incorporating the carbon additive onto the silica fiber powder after fragmentation of the silica fiber mat.
[0040] Forming the cathode region may include, consist essentially of, or consist of the following steps: (i) electrospinning a sol-gel to form a silica fiber mat, and (ii) fragmenting the mat to form a silica fiber powder. The silica fiber powder may include, consist essentially of, or consist of particles and / or fiber fragments that may have an average size (e.g., average diameter, length, width, or other size) in the range of about 20 μm to about 200 μm. The silica fiber powder may include, consist essentially of, or consist of a plurality of fiber fragments, each of which is composed of a plurality of silica fibers or portions thereof. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 50 nm to about 5 μm. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 200 nm to about 1000 nm. The silica fiber powder may consist essentially of or consist of SiO2.
[0041] Sol-gel can be prepared with tetraethyl orthosilicate (TEOS). Before electrospinning sol-gel, sol-gel can be produced by an initial sol, which comprises, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst. The initial sol may comprise, and consist essentially of or consist of, 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water. The initial sol may comprise, and consist essentially of or consist of, about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water. The acid catalyst may comprise, and consist essentially of or consist of, HCl. The initial sol may comprise an acid catalyst less than about 0.1% by weight. The initial sol may comprise an acid catalyst of 0.02% to 0.08% by weight. The initial sol may contain one or more agents that alter one or more properties of the initial sol, the sol-gel, and / or the silica fibers.
[0042] Forming the cathode region may include incorporating the lithium additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat includes the lithium additive incorporated therein. Forming the cathode region may include incorporating the lithium additive onto the silica fibers during electrospinning of the silica fibers. Forming the cathode region may include incorporating the lithium additive onto the silica fiber mat prior to fragmentation of the silica fiber mat. Forming the cathode region may include incorporating the lithium additive onto the silica fiber powder after fragmentation of the silica fiber mat.
[0043] In yet another aspect, embodiments of the invention feature a charge storage device that includes, consists essentially of, or consists of an anode region, a cathode region, and a separator disposed between the anode region and the cathode region. The anode region includes, consists essentially of, or consists of carbon. The cathode region includes, consists essentially of, or consists of lithium. The separator includes an electrolyte material. The separator includes (i) one or more silica fiber sheets, and (ii) a polymer layer, consists essentially of, or consists of.
[0044] Embodiments of the present invention may include one or more of the following in any combination in various combinations. The carbon additive may include, consist essentially of, or consist of graphene, amorphous carbon, and / or graphite. The lithium additive may include, consist essentially of, or consist of lithium metal oxide and / or lithium metal phosphate. The electrolyte material may include, consist essentially of, or consist of an organic solvent and a lithium salt. The electrolyte material may include, consist essentially of, or consist of a lithium salt. The separator may include (i) a first silica fiber sheet, (ii) a second silica fiber sheet, and (iii) a polymer layer disposed between the first silica fiber sheet and the second silica fiber sheet, consisting essentially of, or consisting of.
[0045] The one or more silica fiber sheets may be formed at least in part by electrospinning sol-gel. The sol-gel may be prepared from tetraethyl orthosilicate (TEOS). Prior to electrospinning the sol-gel, the sol-gel may be produced from an initial sol comprising, and essentially consisting of, or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst, and water. The initial sol may comprise, and essentially consisting of, or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst, and water. The initial sol may comprise, and essentially consisting of, or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst, and water. The initial sol may comprise, and essentially consisting of, or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst, and water. The initial sol may comprise, and essentially consisting of, or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst, and water. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and the balance of water. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water, and is essentially composed of or consisting of it. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst, and is essentially composed of or consisting of it. The initial sol may comprise 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water, and is essentially composed of or consisting of it. The initial sol may comprise about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water, and is essentially composed of or consisting of it. The acid catalyst may comprise HCl, and is essentially composed of or consisting of it. The initial sol may contain less than about 0.1 wt % of an acid catalyst. The initial sol may contain 0.02 wt % to 0.08 wt % of an acid catalyst. The initial sol may contain one or more agents that alter one or more properties of the initial sol, sol-gel, and / or silica fibers.
[0046] Producing sol-gel may include transforming the initial sol for at least 2 days under conditions where humidity is in the range of about 40% to about 80% and temperature is in the range of 50°F to 90°F. The initial sol may be allowed to transform for at least 3 days, at least 4 days, at least 5 days, at least 6 days, or at least 7 days. The initial sol may be allowed to transform for 2 to 10 days, and in some embodiments, for 2 to 7 days. When the weight is 20% to 40% of the initial weight of the initial sol or sol-gel before maturation (transformation), the sol-gel may be electrospun. When the generation of ethylene vapor is 10% to 20% of the peak generation of ethylene vapor during the maturation (transformation) of the initial sol or sol-gel before maturation, the sol-gel may be electrospun. When the ethylene vapor generated by the sol-gel is 10% to 40% relative to the initial sol or sol-gel before maturation (transformation), the sol-gel may be electrospun.
[0047] The anode material may include, consist essentially of, or consist of a first silica fiber powder and a carbon additive. The first silica fiber powder may be formed by a process comprising, consisting essentially of, or consisting of the following steps: (i) electrospinning a sol-gel to form a silica fiber mat, and (ii) fragmenting the mat to form a silica fiber powder. The silica fiber powder may include, consist essentially of, or consist of particles and / or fiber fragments having an average size (e.g., average diameter, length, width, or other size) in the range of about 20 μm to about 200 μm. The silica fiber powder may include, consist essentially of, or consist of a plurality of fiber fragments, each of which is composed of a plurality of silica fibers or portions thereof. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 50 nm to about 5 μm. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 200 nm to about 1000 nm. The silica fiber powder may consist essentially of or consist of SiO2.
[0048] Sol-gel can be prepared with tetraethyl orthosilicate (TEOS). Before electrospinning sol-gel, sol-gel can be produced by an initial sol, which comprises, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst. The initial sol may comprise, and consist essentially of or consist of, 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water. The initial sol may comprise, and consist essentially of or consist of, about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water. The acid catalyst may comprise, and consist essentially of or consist of, HCl. The initial sol may comprise an acid catalyst less than about 0.1% by weight. The initial sol may comprise an acid catalyst of 0.02% to 0.08% by weight. The initial sol may contain one or more agents that alter one or more properties of the initial sol, the sol-gel, and / or the silica fibers.
[0049] The process of forming the first silica fiber powder may include incorporating a carbon additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat includes the carbon additive incorporated therein. The process of forming the first silica fiber powder may include incorporating the carbon additive onto the silica fibers during electrospinning of the silica fibers. The process of forming the first silica fiber powder may include incorporating the carbon additive onto the silica fiber mat prior to fragmentation of the silica fiber mat. The process of forming the first silica fiber powder may include incorporating the carbon additive onto the silica fiber powder after fragmentation of the silica fiber mat.
[0050] The cathode material may include, consist essentially of, or consist of a second silica fiber powder and a lithium additive. The second silica fiber powder may be formed by a process comprising, consisting essentially of, or consisting of: (i) electrospinning a sol-gel to form a silica fiber mat, and (ii) fragmenting the mat to form a silica fiber powder. The silica fiber powder may include, consist essentially of, or consist of particles and / or fiber fragments having an average size (e.g., average diameter, length, width, or other size) in the range of about 20 μm to about 200 μm. The silica fiber powder may include, consist essentially of, or consist of a plurality of fiber fragments, each of which is composed of a plurality of silica fibers or portions thereof. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 50 nm to about 5 μm. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 200 nm to about 1000 nm. The silica fiber powder may consist essentially of, or consist of, SiO2.
[0051] Sol-gel can be prepared with tetraethyl orthosilicate (TEOS). Before electrospinning sol-gel, sol-gel can be produced by an initial sol, which comprises, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst. The initial sol may comprise, and consist essentially of or consist of, 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water. The initial sol may comprise, and consist essentially of or consist of, about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water. The acid catalyst may comprise, and consist essentially of or consist of, HCl. The initial sol may comprise an acid catalyst less than about 0.1% by weight. The initial sol may comprise an acid catalyst of 0.02% to 0.08% by weight. The initial sol may contain one or more agents that alter one or more properties of the initial sol, the sol-gel, and / or the silica fibers.
[0052] The process of forming the second silica fiber powder may include incorporating a lithium additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat includes the lithium additive incorporated therein. The process of forming the second silica fiber powder may include incorporating the lithium additive onto the silica fibers during electrospinning of the silica fibers. The process of forming the second silica fiber powder may include incorporating the lithium additive onto the silica fiber mat prior to fragmentation of the silica fiber mat. The process of forming the second silica fiber powder may include incorporating the lithium additive onto the silica fiber powder after fragmentation of the silica fiber mat.
[0053] In another aspect, an embodiment of the invention features a method of making a charge storage device. An anode region is formed. A cathode region is formed. A separator is disposed between the anode region and the cathode region. The anode region includes, consists essentially of, or consists of an anode material. The anode material includes, consists essentially of, or consists of carbon. The cathode region includes, consists essentially of, or consists of a cathode material. The cathode material includes, consists essentially of, or consists of lithium. The separator includes an electrolyte material. The separator includes (i) one or more silica fiber sheets, and (ii) a polymer layer, consisting essentially of or consisting of.
[0054] Embodiments of the present invention may include one or more of the following in any combination in various combinations. The anode material may include, consist essentially of, or consist of graphene, amorphous carbon, and / or graphite. The cathode material may include, consist essentially of, or consist of lithium metal oxide and / or lithium metal phosphate. The electrolyte material may include, consist essentially of, or consist of an organic solvent and a lithium salt. The electrolyte material may include, consist essentially of, or consist of a lithium salt. The separator may include (i) a first silica fiber sheet, (ii) a second silica fiber sheet, and (iii) a polymer layer disposed between the first silica fiber sheet and the second silica fiber sheet, consisting essentially of, or consisting of.
[0055] The one or more silica fiber sheets may be formed at least in part by electrospinning sol-gel. The sol-gel may be prepared from tetraethyl orthosilicate (TEOS). Prior to electrospinning the sol-gel, the sol-gel may be produced from an initial sol comprising, and essentially consisting of, or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst, and water. The initial sol may comprise, and essentially consisting of, or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst, and water. The initial sol may comprise, and essentially consisting of, or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst, and water. The initial sol may comprise, and essentially consisting of, or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst, and water. The initial sol may comprise, and essentially consisting of, or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst, and water. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and the balance of water. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water, and is essentially composed of or consisting of it. The initial sol may comprise 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst, and is essentially composed of or consisting of it. The initial sol may comprise 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water, and is essentially composed of or consisting of it. The initial sol may comprise about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water, and is essentially composed of or consisting of it. The acid catalyst may comprise HCl, and is essentially composed of or consisting of it. The initial sol may contain less than about 0.1 wt % of an acid catalyst. The initial sol may contain 0.02 wt % to 0.08 wt % of an acid catalyst. The initial sol may contain one or more agents that alter one or more properties of the initial sol, sol-gel, and / or silica fibers.
[0056] Producing sol-gel may include transforming the initial sol for at least 2 days under conditions where humidity is in the range of about 40% to about 80% and temperature is in the range of 50°F to 90°F. The initial sol may be allowed to transform for at least 3 days, at least 4 days, at least 5 days, at least 6 days, or at least 7 days. The initial sol may be allowed to transform for 2 to 10 days, and in some embodiments, for 2 to 7 days. When the weight is 20% to 40% of the initial weight of the initial sol or sol-gel before maturation (transformation), the sol-gel may be electrospun. When the generation of ethylene vapor is 10% to 20% of the peak generation of ethylene vapor during the maturation (transformation) of the initial sol or sol-gel before maturation, the sol-gel may be electrospun. When the ethylene vapor generated by the sol-gel is 10% to 40% relative to the initial sol or sol-gel before maturation (transformation), the sol-gel may be electrospun.
[0057] The anode material may include, consist essentially of, or consist of a first silica fiber powder and a carbon additive. The first silica fiber powder may be formed by a process comprising, consisting essentially of, or consisting of the following steps: (i) electrospinning a sol-gel to form a silica fiber mat, and (ii) fragmenting the mat to form a silica fiber powder. The silica fiber powder may include, consist essentially of, or consist of particles and / or fiber fragments having an average size (e.g., average diameter, length, width, or other size) in the range of about 20 μm to about 200 μm. The silica fiber powder may include, consist essentially of, or consist of a plurality of fiber fragments, each of which is composed of a plurality of silica fibers or portions thereof. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 50 nm to about 5 μm. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 200 nm to about 1000 nm. The silica fiber powder may consist essentially of or consist of SiO2.
[0058] Sol-gel can be prepared with tetraethyl orthosilicate (TEOS). Before electrospinning sol-gel, sol-gel can be produced by an initial sol, which comprises, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst. The initial sol may comprise, and consist essentially of or consist of, 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water. The initial sol may comprise, and consist essentially of or consist of, about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water. The acid catalyst may comprise, and consist essentially of or consist of, HCl. The initial sol may comprise an acid catalyst less than about 0.1% by weight. The initial sol may comprise an acid catalyst of 0.02% to 0.08% by weight. The initial sol may contain one or more agents that alter one or more properties of the initial sol, the sol-gel, and / or the silica fibers.
[0059] Forming the anodic region may include incorporating the carbon additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat includes the carbon additive incorporated therein. Forming the anodic region may include incorporating the carbon additive onto the silica fibers during electrospinning of the silica fibers. Forming the anodic region may include incorporating the carbon additive onto the silica fiber mat prior to fragmentation of the silica fiber mat. Forming the anodic region may include incorporating the carbon additive onto the silica fiber powder after fragmentation of the silica fiber mat.
[0060] The cathode material may include, consist essentially of, or consist of a second silica fiber powder and a lithium additive. The second silica fiber powder may be formed by a process comprising, consisting essentially of, or consisting of: (i) electrospinning a sol-gel to form a silica fiber mat, and (ii) fragmenting the mat to form a silica fiber powder. The silica fiber powder may include, consist essentially of, or consist of particles and / or fiber fragments having an average size (e.g., average diameter, length, width, or other size) in the range of about 20 μm to about 200 μm. The silica fiber powder may include, consist essentially of, or consist of a plurality of fiber fragments, each of which is composed of a plurality of silica fibers or portions thereof. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 50 nm to about 5 μm. The fibers or portions thereof within the silica fiber powder may have a variable diameter of about 200 nm to about 1000 nm. The silica fiber powder may consist essentially of, or consist of, SiO2.
[0061] Sol-gel can be prepared with tetraethyl orthosilicate (TEOS). Before electrospinning sol-gel, sol-gel can be produced by an initial sol, which comprises, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol can comprise, and is essentially composed of or consisting of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, an acid catalyst and water. The initial sol may comprise, and consist essentially of or consist of, 70% to 90% by weight of TEOS, 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst. The initial sol may comprise, and consist essentially of or consist of, 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water. The initial sol may comprise, and consist essentially of or consist of, about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water. The acid catalyst may comprise, and consist essentially of or consist of, HCl. The initial sol may comprise an acid catalyst less than about 0.1% by weight. The initial sol may comprise an acid catalyst of 0.02% to 0.08% by weight. The initial sol may contain one or more agents that alter one or more properties of the initial sol, the sol-gel, and / or the silica fibers.
[0062] Forming the cathode region may include incorporating the lithium additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat includes the lithium additive incorporated therein. Forming the cathode region may include incorporating the lithium additive onto the silica fibers during electrospinning of the silica fibers. Forming the cathode region may include incorporating the lithium additive onto the silica fiber mat prior to fragmentation of the silica fiber mat. Forming the cathode region may include incorporating the lithium additive onto the silica fiber powder after fragmentation of the silica fiber mat.
[0063] By reference to the following description, drawings and claims, these and other objects disclosed herein and the advantages and features of the present invention will become more apparent. In addition, it should be understood that the features of the various embodiments described herein are not mutually exclusive and may exist in various combinations and arrangements. As used herein, the terms "approximately", "about" and "substantially" refer to ±10%, and in some embodiments, ±5%. Unless otherwise defined herein, the term "substantially composed of..." refers to the exclusion of other materials that contribute to the function. However, such other materials may exist together or alone in trace amounts. Unless otherwise indicated, the charge storage devices described herein, such as batteries, materials, mixtures, regions and other structures may incorporate unintentional impurities. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] In the accompanying drawings, similar reference characters generally refer to the same parts throughout the different views. Moreover, the drawings are not necessarily drawn to scale, but emphasis is generally placed on illustrating the principles of the invention. In the following description, various embodiments of the invention are described with reference to the following drawings, in which:
[0065] Figure 1A is a schematic cross-sectional view of a battery according to an embodiment of the present invention.
[0066] Figure 1B is a schematic cross-sectional view of a battery having a coin cell form factor according to an embodiment of the present invention.
[0067] Figure 2A-2D is a scanning electron microscope (SEM) image of a fiber spun according to an embodiment of the present invention. Figure 2A-2D The images in the figure are at scales of 50 μm, 100 μm, 200 μm, and 500 μm.
[0068] Figure 3 The fiber spun according to the embodiment of the present invention has a ripening ratio of Figure 2A-2D The figures shown are SEM images after even shorter times (shown at 20 micron scale).
[0069] Figure 4 A fiber mat having a thickness of about 1 / 4 inch spun according to an embodiment of the present invention is shown.
[0070] Figure 5A and Figure 5B The silica fiber mats electrospun after longer transition times according to embodiments of the present invention were compared ( Figure 5A ) and a fiber mat electrospun after a shorter transition time according to other embodiments of the present invention ( Figure 5B ).
[0071] Fig. 6A and Figure 6B A SEM image of fiber dust according to an embodiment of the present invention is shown, wherein a 100 μm scale is shown. DETAILED DESCRIPTION
[0072] According to various embodiments of the present invention, silica fibers and / or powders formed therefrom are used as structural matrices (or at least a portion thereof) of various components of batteries or other charge storage devices (e.g., supercapacitors). Various components of the battery incorporate other materials mixed with, applied to, and / or incorporated into the silica fibers to achieve electrochemical charge storage and conductivity of the battery. The silica fibers themselves may be made of a colloidal material that is electrospun to form a fiber mat. The mat itself (or a portion thereof) may be used in a battery with or without additional processing (e.g., pressing and / or incorporation of additive materials). In various embodiments, the mat is fragmented into a powder or dust that may include, consist essentially of, or consist of fiber fragments. The powder, which may have been incorporated with one or more additive materials introduced before, during, or after the fiber electrospinning process, may be used in one or more regions of the battery. In various embodiments, the powder is mixed with one or more additives for use in one or more battery regions. In other embodiments, the powder is pressed into a planar sheet and used in a battery with or without incorporation of one or more additives.
[0073] In some embodiments, the silica fibers and / or fiber mats are electrospun from colloidal materials. For example, the silica fibers and / or fiber mats can be prepared by electrospinning a sol-gel, which can be prepared using a silane oxide reagent such as tetraethyl orthosilicate (TEOS), an alcohol solvent, and an acid catalyst.
[0074] In some embodiments, the sol-gel for preparing the silica fiber composition is prepared by the following method, which includes: preparing a first mixture comprising an alcohol solvent, a silane oxide reagent such as tetraethyl orthosilicate (TEOS); preparing a second mixture comprising an alcohol solvent, water and an acid catalyst; completely titrating the second mixture into the first mixture; and processing (aging) the combined mixture to form a gel for electrospinning. In some embodiments, the silane oxide reagent is TEOS. Alternative silane oxide reagents include those having the formula Si(OR)4, wherein R is 1-6, and preferably 1, 2 or 3.
[0075] In some embodiments, the sol comprises, consists essentially of, or consists of about 70% to about 90% by weight of a silane oxide (e.g., TEOS), about 5% to about 25% by weight of an alcohol solvent (e.g., anhydrous ethanol), an acid catalyst (e.g., less than about 0.1% by weight when HCl is used), and water. Any sol or sol-gel described herein may include a balance of water (i.e., water may constitute any amount not originally specified for the sol or sol-gel). Any sol or sol-gel described herein may optionally include one or more reagents or additives that may or do alter one or more properties of the sol, sol-gel, and / or silica fiber (and / or powder prepared therefrom). Such reagents may include, but are not limited to, for example, polymers and polymer solutions, inert reagents, alcohols, organic and / or aqueous solvents, organic salts, inorganic salts, metals, metal oxides, metal nitrides, metal oxynitrides, carbon (e.g., graphene, graphite, amorphous carbon, fullerenes, etc.), and the like.
[0076] In some embodiments, the colloidal sol comprises 70% to 90% by weight of tetraethyl orthosilicate (TEOS), 8% to 25% by weight of ethanol, 1% to 10% by weight of water and an acid catalyst. In some embodiments, the colloidal sol comprises 75% to 85% by weight of TEOS, 12% to 20% by weight of ethanol and about 2% to 5% by weight of water. Exemplary colloidal sol comprises about 80% by weight of TEOS, about 17% by weight of ethanol and about 3% by weight of water. In some embodiments, the acid catalyst is HCl. For example, the colloidal sol may comprise less than about 0.1% by weight of HCl. For example, the colloidal sol may comprise 0.02% to 0.08% by weight of HCl. In various embodiments, the colloidal sol does not comprise organic polymers or other substantial reagents so that the fiber composition will be substantially pure SiO . In various embodiments, the sol does not contain inorganic salts (e.g., sodium chloride, lithium chloride, potassium chloride, magnesium chloride, calcium chloride, and / or barium chloride), nor does the sol contain inorganic salts mixed with other components of the sol or mixed into the sol itself. In various embodiments, the fiber composition does not contain metals or metal oxides (e.g., TiO2 or ZrO2). In various embodiments, the fiber composition consists essentially of SiO2, i.e., only contains SiO2 and unintentional impurities and, in some embodiments, substances and / or complexes resulting from incomplete conversion of the sol to SiO2 (e.g., water and / or chemical groups such as ethoxy, silanol, hydroxyl, etc.). In various embodiments, additives can be incorporated into the silica fibers and / or powders prepared therefrom after the electrospinning process.
[0077] In some embodiments, the alcohol solvent is anhydrous denatured ethanol, or in some embodiments, is methanol, propanol, butanol or any other suitable alcohol solvent. The first mixture can be stirred, for example, using a magnetic stirrer, a vibrating platform or a vibrating platform or other stirring tools. The second mixture comprises an alcohol solvent, water and an acid catalyst. The alcohol solvent can be anhydrous denatured alcohol, or can be methanol, propanol, butanol or any other suitable alcohol solvent provided. Water can be distilled water or deionized water. Enough acid catalysts are added to the mixture to help the reaction. The acid catalyst can be hydrochloric acid, or can be sulfuric acid or other suitable acid catalysts. The second mixture can be stirred, for example, with a magnetic stirrer, a vibrating platform or a vibrating platform or other stirring tools. In some embodiments, the first mixture (or colloidal sol) and the second mixture (or colloidal sol) are produced without using direct heating (that is, heat applied by an external tool such as a hot plate or other heat source).
[0078] According to various embodiments, by dripping or titrating the second mixture into the first mixture, preferably under agitation the first mixture and the second mixture are merged.Then by making the sol slaking in a controlled environment until most of the alcohol solvent evaporates, to produce the sol-gel suitable for electrospinning, further process the merged mixture.For example, a controlled environment may include a housing with at least one vent and an optional fan that extracts gas from the mixture, and this may relate to humidity, temperature and the controlled conditions of optional atmospheric pressure.For example, humidity may be controlled (for example, by using conventional humidifiers and / or dehumidifiers) in the range of about 30% to about 90% such as about 40% to about 80%, or in some embodiments about 50% to about 80%, or about 50% to about 70% (for example, about 55%, or about 60%, or about 65%). Certain humidity may help to slow down the evaporation of the solvent, thereby extending the window of successful electrospinning. In some embodiments, the temperature is in the range of about 50°F to about 90°F, such as about 60°F to about 80°F, or about 65°F to about 75°F. In various embodiments, the sol is not exposed to heat exceeding 150°F or heat exceeding 100°F to avoid accelerated transformation. In some embodiments, the atmospheric pressure is optionally controlled (e.g., using a low-pressure vacuum source such as a pump or fan). By controlling the environmental conditions during the aging process, the time period in which the gel can be electrospun can be extended; if the aging process is too fast (such as due to direct heating), the time period may be a small window of only a few minutes. When the sol is aged at a constant humidity of about 55% and a temperature of about 72°F, the sol will mature (gel) within a few days, and the window for successful electrospinning can be extended to at least a few hours, and in some embodiments to a few days. In various embodiments, the aging process requires at least 2 days, or at least 3 days in some embodiments. However, in various embodiments, the aging does not need to exceed 10 days, or more than 7 days. In some embodiments, the aging process requires 2 to 10 days, or 2 to 7 days, or 2 to 5 days, or 2 to 4 days (e.g., about 2, about 3, or about 4 days). In various embodiments, the sol-gel is fully spinnable before transforming into a more solidified, non-flowable mass.
[0079] The housing space for ripening the sol-gel may include vents on at least one surface for exhausting gases from the housing, and optionally, the vents may include fans for exhausting gases generated during the ripening process. The housing space may optionally include a heating source (e.g., one or more heating elements, such as a resistive heating element) for providing nominal heat in the housing space to maintain a preferred temperature. In some embodiments, a humidity source (e.g., an open container of water or other aqueous, water-based liquid) is provided in the housing environment to adjust the humidity to a desired range or value. The housing may also include one or more environmental monitors, such as a temperature reading device (e.g., a thermometer, a thermocouple or other temperature sensor) and / or a humidity reading device (e.g., a hygrometer or other humidity sensor).
[0080] In some embodiments, the sol-gel is electrospun after a aging process of at least 2 days, or at least 36 hours, or at least 3 days, or at least 4 days, or at least 5 days (but in various embodiments, no more than 10 days or no more than 7 days under controlled environmental conditions) under controlled environmental conditions. By slowing down the aging process, the ideal time for spinning fibers can be determined. The weight of the sol-gel can be used as an indicator of when the sol-gel reaches or approaches the ideal time for electrospinning. Without being bound by theory, it is believed that the viscosity of the sol-gel is a poor determining factor for determining the best time for electrospinning. For example, in various embodiments, the sol-gel is about 10% to about 60% of the original weight of the sol (based on the loss of alcohol solvent during the transition). In some embodiments, the sol-gel is 15% to 50% of the original weight of the sol, or in the range of about 20% to about 40% of the original weight of the sol.
[0081] In some embodiments, the sol-gel is ripened for at least 2 days, or at least 36 hours, or at least 3 days, or at least 4 days, or at least 5 days, and the ethylene vapor produced by the composition is electrospun when it is between about 10% to about 40% of the steam produced by the starting sol (such as in the range of about 10% to about 25% or in the range of about 10% to about 20%). Ethylene is a colorless, flammable gas with a light sweet and musky smell (when solvent evaporation slows down, this is very obvious). Ethylene is produced by ethanol and acid reaction. Optionally, conventional ethylene monitors can be used to monitor the ethylene in the steam. In other embodiments, the gas produced by the sol during the sol ripening process is monitored to determine the appropriate or optimal time for electrospinning. Gas chromatography can be used to monitor gas profiles.
[0082] In various embodiments, additives such as carbon additives and / or lithium additives may be introduced into the sol-gel prior to electrospinning, and such additives may thus be incorporated into and / or onto the spun fibers. In various embodiments, the additives are introduced into the sol-gel immediately prior to electrospinning (e.g., less than 0.5 hours prior, less than 1 hour prior, less than 2 hours prior, or less than 5 hours prior), so that the sol-gel is successfully matured prior to the introduction of the additives, thereby facilitating successful electrospinning. In various embodiments, the additives may be introduced into the sol-gel after the sol-gel has been matured for at least 0.5 days, at least 1 day, at least 2 days, or at least 3 days.
[0083] In various embodiments, the sol-gel can be matured in a shorter time, as long as the sol-gel remains spinnable by electrospinning. After being matured in a shorter time, the resulting silica fiber mat or fiber assembly may be more brittle in some cases, but such brittleness may not prevent fiber fragmentation and the generation of powder thereby. In various embodiments, the silica fiber powder used in one or more regions of the battery can be produced by electrospinning silica fibers or fiber mats after a shorter maturation time than the maturation time of the silica fibers or fiber mats used in the form of mats or sheets in the battery. For example, the silica fiber powder used in one or more regions of the battery can be produced by electrospinning silica fibers or fiber mats that are less than 2 days or less than 1 day after maturation.
[0084] Due to the formation of silicon dioxide crystalline material on the top surface of the mixture, the processing of the sol-gel mixture may require stirring or other agitation of the mixture at various intervals or continuously. This formation of crystalline material on the top surface slows down the processing time, and it is believed that the crystalline material seals the gaseous vacuum provided in the shell space to which the mixture is exposed. In some embodiments, any solid crystalline material is removed from the mixture.
[0085] After the sol-gel process is complete, the sol-gel is then electrospun using any known technique. If desired, the sol or sol-gel may be stored (e.g., frozen or refrigerated) (and such time is generally not applicable to aging time). Exemplary processes for electrospinning sol-gels are described in Choi, Sung-Seen et al., Silica nanofibers from electrospinning / sol-gel process , Journal of Materials Science Letters 22, 2003, 891-893, which is hereby incorporated by reference in its entirety. An exemplary process for electrospinning is also disclosed in U.S. Pat. No. 8,088,965, which is hereby incorporated by reference in its entirety.
[0086] In an exemplary electrospinning technique, the sol-gel is placed in one or more injection pumps that are fluidically connected to one or more spinnerets. The spinneret is connected to a high voltage (e.g., 5kV to 50kV) source, and is outside a grounded collection drum and facing a grounded collection drum. During spinning, the drum is usually rotated along a rotation axis approximately perpendicular to the spinning direction extending from the spinneret to the drum. When the sol-gel is supplied to the spinneret from a syringe pump (or other storage tank), the high voltage between the spinneret and the drum forms a charged liquid jet, which is deposited on the drum as small entangled fibers. Along with the rotation of the drum and the continuation of electrospinning, a fiber mat of silica fibers is formed around the periphery of the drum. In various embodiments, the spinneret and the injection pump may be arranged on a movable platform, which may be movable parallel to the length of the drum. In this way, without increasing the number of spinnerets, the length of the resulting fiber mat may be increased along the drum. The diameter of the drum may also be increased to increase the area size of the electrospun mat. The thickness of the mat can depend largely on the amount of sol-gel used for spinning, and therefore on the amount of electrospinning time. For example, the mat can have a thickness greater than about 1 / 8 inch, or greater than about 1 / 4 inch, or greater than about 1 / 3 inch, or greater than about 1 / 2 inch.
[0087] After completing the electrospinning process, the resulting pad is taken out from the drum. For example, the pad can be cut into one or more fragments and peeled off from the drum. The pad can then be fragmented to form a powder. In various embodiments, the powder includes small fiber fragments, is essentially composed of or is composed of it, and the small fiber fragments are each an interwoven collection of silica fibers rather than a single solid particle. In some embodiments, the electrospun pad can be broken, cut, ground, milled or otherwise divided into small fragments that retain the fiber structure. In some embodiments, the pad (or one or more parts thereof) is rubbed by one or more screens or sieves, and the mesh size of the screen determines at least in part the size of the resulting fiber fragments or powder or dust produced by the electrospun pad. For example, a pad or a pad portion can be rubbed by two or more continuous screens (for example, a screen with a mesh number of 100, 200, 300 or even 400) with a mesh size decreasing, to produce powder or dust or a collection of fiber fragments with a desired size.
[0088] In various embodiments, one or more additives are introduced to the silica fibers during the electrospinning process. For example, a slurry containing the material (e.g., in powder or granular form) can be sprayed or atomized onto the fibers between the spinneret and the drum, or formed on the drum itself. In various embodiments, the slurry contains one or more additives selected for the desired region of the battery and a carrier such as water and / or an organic liquid such as propylene carbonate in solution. Batteries according to embodiments of the present invention may also incorporate one or more regions or sheets of spun silica fibers (or powders produced therefrom) without additives.
[0089] In various embodiments, additives may be added to the sol-gel, e.g., in particulate or powder form, or as a slurry or mixture, prior to spinning of the silica fibers, and the as-spun fibers will incorporate the additives therein or thereon. In various embodiments, the additives are added to the sol-gel after at least a portion of the aging time.
[0090] In other embodiments, the additive is incorporated into the silica fiber and / or powder after the fiber or fiber mat is spun. After the electrospinning process is completed, the resulting mat is removed from the drum. For example, the mat can be cut into one or more fragments and peeled off the drum. If necessary or desired, the mat can be cut into a certain size, and the electrospun mat of silica fibers can be coated with one or more additives to form a region of a battery or other charge storage device. For example, the additive can be deposited on the silica fiber by techniques such as electrodeposition, atomic layer deposition, chemical vapor deposition from a solution containing the additive, or by spraying or atomizing a solution containing one or more additives selected for the desired region of the battery with a carrier such as water and / or a polymer binder. In various embodiments, the silica fiber or mat is processed into a silica fiber powder, and the additive is deposited on the powder (e.g., by any of the above techniques) and / or mixed with the powder.
[0091] Figure 1A is a schematic diagram of a battery 100 according to an embodiment of the present invention. As shown, the battery 100 features an anode region 110, a cathode region 120, and a separator 130 located between the anode region 110 and the cathode region 120. In the depicted embodiment, the separator 130 includes a polymer layer 140, a first silica fiber sheet 150, and a second silica fiber sheet 160. However, various embodiments of the present invention lack the first silica fiber sheet 150 and / or the second silica fiber sheet 160. Figure 1B1 is a schematic cross-sectional view of a battery 100 having a coin cell form factor. As shown, the battery 100 is disposed within a housing or shell that includes a top 170 corresponding to the negative terminal of the battery and a bottom 180 corresponding to the positive terminal of the battery. Thus, portions 170, 180 may be conductive and electrically connected to anode 110 and cathode 120. Thus, housing portions 170, 180 may be used to power an external load and / or recharge the battery 100 by applying current from an external power source. A seal 190 may be present to facilitate sealing the housing.
[0092] In various embodiments, the anode region 110 includes, consists essentially of, or consists of silica fiber powder and a carbon additive (e.g., silica fiber powder with the carbon additive incorporated thereon). For example, the carbon additive may include, consists essentially of, or consists of graphene, amorphous carbon, and / or graphite. In other embodiments, such as those featuring silica fiber powder and / or sheets in other regions of the cell, the anode region 110 is substantially free of silica fiber powder; for example, the anode region 110 may include, consists essentially of, or consists of a carbon additive (e.g., in powder or pressed powder / solid form) with or without another support.
[0093] In various embodiments of the present invention, the anode region 110 can be prepared by mixing the desired composition with a binder and / or a solvent to form a uniform slurry. The slurry can be cast on a flat surface (e.g., a metal (e.g., copper) sheet or foil and / or a glass sheet) and spread to a uniform thickness. The slurry can then be dried to evaporate and substantially remove the binder and / or solvent. In various embodiments, a trace amount (e.g., less than 0.1%, less than 0.01% or less than 0.001% by weight or volume) of a binder and / or solvent may be present in the final anode region 110. The coated metal foil can be cut (e.g., stamped) into a desired size and shape (e.g., a disc) to form the anode region 110, which can be assembled with the cathode region 120 and the separator 130.
[0094] In various embodiments, the cathode region 120 includes, consists essentially of, or consists of a silica fiber powder and a lithium additive (e.g., a silica fiber powder having a lithium additive incorporated thereon). For example, the lithium additive may include, consists essentially of, or consists of a lithium metal oxide (e.g., a lithium transition metal oxide such as lithium cobalt oxide or lithium manganese oxide) or a lithium metal phosphate (e.g., lithium iron phosphate). Exemplary lithium additives according to embodiments of the present invention include lithium metal oxides such as lithium cobalt oxide, and / or lithium manganese oxide, and / or lithium metal phosphates such as lithium iron phosphate. In various embodiments, the lithium additive includes, consists essentially of, or consists of a lithium metal oxide salt such as LiNiMnCoO2 (NMC), LiNiCoAlO2 (NCA), LiCoO2 (LCO), LiFePO4 (LFP), etc. In other embodiments, such as those featuring silica fiber powders and / or sheets in other regions of the cell, the cathode region 120 is substantially free of silica fiber powder; for example, the cathode region 120 can include, consist essentially of, or consist of a lithium additive (e.g., in powder or pressed powder / solid form) with or without another support. In various embodiments, the cathode region 120 can also include a carbon additive, such as amorphous carbon or graphitic carbon.
[0095] In various embodiments of the present invention, cathode region 120 can be prepared by mixing the desired composition with a binder and / or solvent to form a uniform slurry. The slurry can be cast on a flat surface (e.g., a metal (e.g., aluminum) sheet or foil and / or a glass sheet) and spread to a uniform thickness. The slurry can then be dried to evaporate and substantially remove the binder and / or solvent. In various embodiments, trace amounts (e.g., less than 0.1%, less than 0.01%, or less than 0.001% by weight or volume) of binder and / or solvent may be present in the final cathode region 120. The coated metal foil can be cut (e.g., stamped) into a desired size and shape (e.g., a disc) to form a cathode region 120, which can be assembled with anode region 110 and separator 130.
[0096] Separator 130 may include, consist essentially of, or consist of a polymer layer 140, which is generally porous to enable charge transfer (e.g., by the flow of ionic charge carriers). For example, the size of the pores in polymer layer 140 may range from about 5 nm to about 100 nm. Polymer layer 140 may include, consist essentially of, or consist of, for example, one or more polymer materials such as polyethylene, polypropylene, polytetrafluoroethylene, polyvinyl chloride, and / or a polymer blend including one or more of these with or without one or more other polymer materials.
[0097] like Figure 1A and Figure 1B As shown, in various embodiments, the separator 130 may additionally incorporate one or more silica fiber sheets 150, 160. For example, a first silica fiber sheet 150 may be disposed between (and, for example, in direct mechanical contact with) the polymer layer 140 and the anode region 110, and / or a second silica fiber sheet 160 may be disposed between (and, for example, in direct mechanical contact with) the polymer layer 140 and the cathode region 120. In various embodiments, incorporating one or more silica fiber sheets 150, 160 protects the polymer layer 140 from thermal decomposition and / or deformation, enhances the mechanical integrity of the internal structure of the battery 100, and / or improves ion mobility within the battery 100.
[0098] In various embodiments, such as those including one or more silica fiber sheets 150 , 160 , the cell 100 can be substantially free of silica fibers and / or silica fiber powder within the anode region 110 and / or the cathode region 120 .
[0099] In various embodiments, the separator 130 incorporates an electrolyte material that enables charge transfer between the anode region 110 and the cathode region 130 via ionic charge transfer. For example, the electrolyte material may include, consist essentially of, or consist of a mixture of an organic solvent (e.g., ethylene, dimethyl / ethyl carbonate, and / or N-methyl-2-pyrrolidone) and one or more ionic conductors (e.g., a lithium salt such as lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate monohydrate (LiAsF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), or lithium trifluoromethanesulfonate (LiCF3SO3)).
[0100] Example
[0101] Example 1: Preparation of silica fiber mat
[0102] Silica fibers are prepared using an electrospinning process, in which a sol-gel is spun onto a collecting drum to form a nonwoven mat of fibers. The sol-gel is prepared in two parts. First, TEOS is mixed with ethanol, and then a second mixture comprising HCl, water, and ethanol is titrated into the mixture. The sol-gel is then aged for several days under controlled conditions before spinning.
[0103] In one embodiment, a first sol is prepared by weighing 384 grams of TEOS 98% and 41.8 grams of anhydrous denatured ethanol and pouring them together. The first sol is allowed to stand in a beaker and a magnetic stirrer is used to produce a uniform solution. A second sol is prepared by weighing 41.8 grams of anhydrous denatured ethanol, 16.4 grams of distilled water, and 0.34 grams of hydrochloric acid, then pouring them together and mixing them with a magnetic stirrer for 8 seconds until a uniform second sol is formed.
[0104] The second sol is then poured into a titration apparatus, which is placed above the beaker containing the first sol. The titration apparatus then drips about 5 drops per second until a third sol is formed by mixing the first sol and the second sol. During the dripping process, the first sol is continuously mixed with a magnetic stirrer while the second sol is dripped into the first sol.
[0105] The combined third sol is then placed in an enclosure box. A low pressure vacuum is provided by a medium speed fan to remove mist. The air temperature in the box is 72°F and the humidity is 60%. The third sol is left to stand and processed for about three days. The mixture is stirred every day to reduce the accumulation of crystalline structures. As the alcohol solvent evaporates, the third sol begins to transform into a sol-gel. The sol-gel can be monitored to determine the approximate amount of C2H4 (ethylene) in the vapor, which can be in the range of about 10% to 20% relative to the amount of the original sol before aging. After appropriate gelation, the sol-gel is loaded into an electrospinning machine or frozen for electrospinning. In this embodiment, appropriate gelation occurs when the total mass of the sol-gel is between about 70 grams and about 140 grams. This embodiment can be appropriately scaled, and the range can vary, but still produces the desired structure. In order to further determine the ideal time for electrospinning, a portion of the gel can be dripped into the electric field of the spinning device to evaluate the spinning characteristics of the sol-gel.
[0106] Figure 2A-2D is a scanning electron microscope (SEM) image of a fiber spun according to an embodiment of the present invention (50 micron, 100 micron, 200 micron and 500 micron scales are shown). As shown, the fiber is flexible, smooth, dense and continuous (no obvious fragmentation). Figure 3 is an SEM image of a fiber electrospun after a shorter aging time (showing a 20 micron scale), where the fiber is significantly rigid, with many cracks evident. In various embodiments, such fibers may be more brittle and easier to process into silica fiber powder. Figure 4 A fiber mat spun according to an embodiment of the present invention is shown. The flexibility and continuity of the fibers allow the mat to be spun to a thickness of 1 / 4 inch or greater. The mat has a soft, flexible texture.
[0107] Figure 5A and Figure 5Bis a graph depicting the change in properties of silica fiber mats as a function of aging time. Figure 5A The mat of is an example of a mat electrospun for at least 2-3 days according to an embodiment of the present invention, while Figure 5B The mat of is an example of a mat electrospun after a shorter maturation time. Figure 5A The material in the mixture has a soft texture and is very flexible; such material can still be processed into fiber dust or used in sheet form. Figure 5B The material in is brittle, inflexible and thin, and can be easily processed into fiber dust.
[0108] A silica fiber mat is produced and broken into fragments by rubbing through a series of screens of decreasing mesh size. The final screen is a 200 mesh screen, resulting in fiber dust and / or fiber fragments having a size of about 20 μm to about 200 μm. Fig. 6A and Figure 6B An SEM image of the resulting fiber dust is shown, where a 100 μm scale is shown.
[0109] Example 2: Preparation of coin-type battery
[0110] The cathode material of the battery is made by mixing the appropriate amount of active material (e.g., one or more lithium metal oxide salts), amorphous carbon or graphite carbon, and silica fiber powder, weighing it and mixing it with a binder (e.g., PVDF, CMC, SBR, etc.) and a solvent (e.g., NMP) into a uniform slurry with a suitable viscosity (e.g., to allow subsequent spreading for casting). Exemplary embodiments include, for example, about 75% to about 80% active material, 0% to about 10% amorphous carbon or graphite carbon, and about 0.5% to about 10% silica fiber powder prepared as described in Example 1.
[0111] The slurry is cast on a clean, bubble-free battery-grade aluminum foil placed on a glass sheet and spread evenly with a scraper. The slurry is dried to remove the binder and solvent. Exemplary drying conditions include, for example, a drying temperature range of about 80° C. to about 120° C. and a drying time range of about 2 hours to about 4 hours. The resulting coated metal foil is punched into small discs (e.g., having a diameter in the range of about 12 mm to about 30 mm) and weighed.
[0112] The anode material of the battery is manufactured by mixing the appropriate amount of conductive amorphous carbon or graphite carbon and silica fiber powder, weighing it and mixing it with a binder (e.g., PVDF, CMC, SBR, etc.) and a solvent (e.g., NMP) into a uniform slurry with a suitable viscosity (e.g., to allow subsequent spreading for casting). The slurry is cast on a clean, bubble-free battery-grade copper foil placed on a glass sheet and spread evenly with a scraper. The slurry is dried to remove the binder and solvent. Exemplary drying conditions include, for example, a drying temperature range of about 80° C. to about 120° C. and a drying time range of about 2 hours to about 4 hours. The resulting coated metal foil is punched into small discs (e.g., having a diameter in the range of about 12 mm to about 30 mm).
[0113] The battery separator is manufactured by sandwiching a commercially available thin polymer separator sheet between two pressed silica fiber sheets. The sandwich structure is punched into a small disc (e.g., having a diameter in the range of about 12 mm to about 30 mm). The electrolyte is prepared as a solution of a lithium salt in a non-aqueous solvent (e.g., EC, EMC, DEC, DMC, etc.). An exemplary solvent has a concentration in the range of about 0.8 molar concentration to about 2 molar concentration (e.g., about 1 molar concentration). The solvent is introduced onto the separator sandwich structure and absorbed by it.
[0114] Each cell was assembled by sandwiching the separator between the anode and cathode in a glove box under an inert (eg, argon) atmosphere with the metal foils of the anode and cathode each facing away from the separator. The cells were then tested according to industry standards.
[0115] The terms and expressions employed herein are used as descriptive terms and expressions, rather than limiting, and when such terms and expressions are used, it is not intended to exclude any equivalents or portions thereof of the features shown and described. In addition, certain embodiments of the present invention have been described, and it will be apparent to those of ordinary skill in the art that other embodiments incorporating the concepts disclosed herein may be used without departing from the spirit and scope of the present invention. Therefore, the described embodiments should be considered in all respects to be exemplary only and not limiting.
Claims
1. A charge storage device, comprising: an anode region comprising a first silica fiber powder and a carbon additive; a cathode region comprising a second silica fiber powder and a lithium additive; as well as a separator comprising an electrolyte material disposed between the anode region and the cathode region, wherein the separator comprises: (i) one or more silica fiber sheets, and (ii) a polymer layer; The first silica fiber powder or the second silica fiber powder is formed by a process comprising: (i) electrospinning a sol-gel to form a silica fiber mat; and (ii) fragmenting the silica fiber mat to form a silica fiber powder.
2. The charge storage device of claim 1, wherein the carbon additive comprises at least one of graphene, amorphous carbon, or graphite.
3. The charge storage device of claim 1, wherein the lithium additive comprises at least one of a lithium metal oxide or a lithium metal phosphate.
4. The charge storage device of claim 1, wherein the electrolyte material comprises an organic solvent and a lithium salt.
5. The charge storage device of claim 1 , wherein the spacer comprises: (i) a first silica fiber sheet, (ii) a second silica fiber sheet, and (iii) a polymer layer disposed between the first silica fiber sheet and the second silica fiber sheet.
6. The charge storage device of claim 1, wherein the one or more silica fiber sheets are at least partially formed by electrospinning sol-gel.
7. The charge storage device of claim 6, wherein the sol-gel is generated from an initial sol comprising 70% to 90% tetraethyl orthosilicate (TEOS), 8% to 25% anhydrous ethanol, an acid catalyst, and water.
8. The charge storage device of claim 7, wherein the sol-gel is produced at least in part by aging the initial sol at a humidity of 40% to 80% and a temperature of 50°F to 90°F for at least 2 days.
9. The charge storage device of claim 8, wherein the initial sol is aged for at least 3 days.
10. The charge storage device of claim 8, wherein the sol-gel is electrospun when the weight of the sol-gel is in the range of 10% to 60% of the starting weight of the initial sol before ripening.
11. The charge storage device of claim 8, wherein the sol-gel is electrospun when ethylene vapor generated from the sol-gel is in the range of 10% to 40% relative to the initial sol before ripening.
12. The charge storage device of claim 1, wherein the silica fiber powder comprises a plurality of fiber segments, each of the fiber segments being composed of a plurality of silica fibers or portions thereof.
13. The charge storage device of claim 12, wherein the fiber segments have an average size between about 20 μm and about 200 μm.
14. The charge storage device of claim 12, wherein the fibers or portions thereof within the fiber segments have a diameter in the range of about 50 nm to about 5 μm.
15. The charge storage device of claim 12, wherein the fibers or portions thereof within the fiber segments have a diameter in a range of about 200 nm to about 1000 nm.
16. The charge storage device of claim 1, wherein the sol-gel is produced at least in part by ripening an initial sol comprising 70% to 90% tetraethyl orthosilicate (TEOS), 8% to 25% anhydrous ethanol, an acid catalyst, and water.
17. The charge storage device of claim 1, wherein the process of forming the first silica fiber powder comprises incorporating the carbon additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat includes the carbon additive incorporated therein.
18. The charge storage device of claim 1, wherein the process of forming the first silica fiber powder comprises incorporating the carbon additive onto the silica fibers during electrospinning of the silica fibers.
19. The charge storage device of claim 1, wherein the process of forming the first silica fiber powder comprises incorporating the carbon additive onto the silica fiber mat prior to fragmentation of the silica fiber mat.
20. The charge storage device of claim 1, wherein the process of forming the first silica fiber powder comprises incorporating the carbon additive onto the silica fiber powder after fragmentation of the silica fiber mat.
21. The charge storage device of claim 1, wherein the process of forming the second silica fiber powder comprises incorporating the lithium additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat contains the lithium additive incorporated therein.
22. The charge storage device of claim 1, wherein the process of forming the second silica fiber powder comprises incorporating the lithium additive onto the silica fibers during electrospinning of the silica fibers.
23. The charge storage device of claim 1, wherein the process of forming the second silica fiber powder comprises incorporating the lithium additive onto the silica fiber mat prior to fragmentation of the silica fiber mat.
24. The charge storage device of claim 1, wherein the process of forming the second silica fiber powder comprises incorporating the lithium additive onto the silica fiber powder after fragmentation of the silica fiber mat.
25. A method of manufacturing the charge storage device according to claim 1, the method comprising: forming an anode region, the anode region comprising a first silica fiber powder and a carbon additive; forming a cathode region comprising a second silica fiber powder and a lithium additive; and providing a separator comprising an electrolyte material between the anode region and the cathode region, wherein the separator comprises (i) one or more silica fiber sheets, and (ii) a polymer layer; Wherein forming the anode region or cathode region comprises: (i) electrospinning sol-gel to form a silica fiber mat; and (ii) fragmenting the silica fiber mat to form silica fiber powder.
26. The method of claim 25, wherein the carbon additive comprises at least one of graphene, amorphous carbon, or graphite.
27. The method of claim 25, wherein the lithium additive comprises at least one of a lithium metal oxide or a lithium metal phosphate.
28. The method of claim 25, wherein the electrolyte material comprises an organic solvent and a lithium salt.
29. The method of claim 25, wherein the separator comprises: (i) a first silica fiber sheet, (ii) a second silica fiber sheet, and (iii) a polymer layer disposed between the first silica fiber sheet and the second silica fiber sheet.
30. The method of claim 25, further comprising forming the one or more silica fiber sheets at least in part by electrospinning a sol-gel.
31. The method of claim 30, further comprising generating the sol-gel from an initial sol comprising 70% to 90% tetraethyl orthosilicate (TEOS), 8% to 25% anhydrous ethanol, an acid catalyst, and water.
32. The method of claim 31, wherein generating the sol-gel comprises aging the initial sol at a humidity of 40% to 80% and a temperature of 50°F to 90°F for at least 2 days.
33. The method of claim 32, wherein the initial sol is aged for at least 3 days.
34. The method of claim 32, wherein the sol-gel is electrospun when the weight of the sol-gel is in the range of 10% to 60% of the starting weight of the initial sol before ripening.
35. The method of claim 32, wherein the sol-gel is electrospun when ethylene vapor generated from the sol-gel is in the range of 10% to 40% with respect to the initial sol before ripening.
36. The method of claim 25, wherein the silica fiber powder comprises a plurality of fiber segments, each of the fiber segments being comprised of a plurality of silica fibers or portions thereof.
37. The method of claim 36, wherein the fiber fragments have an average size between about 20 μm and about 200 μm.
38. The method of claim 36, wherein the fibers or portions thereof within the fiber fragments have a diameter in the range of about 50 nm to about 5 µm.
39. The method of claim 36, wherein the fibers or portions thereof within the fiber fragments have a diameter in the range of about 200 nm to about 1000 nm.
40. The method of claim 25, further comprising producing the sol-gel by ripening an initial sol comprising 70% to 90% tetraethyl orthosilicate (TEOS), 8% to 25% anhydrous ethanol, an acid catalyst, and water.
41. The method of claim 25, wherein forming the anode region comprises incorporating the carbon additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat comprises the carbon additive incorporated therein.
42. The method of claim 25, wherein forming the anode region comprises incorporating the carbon additive onto the silica fibers during electrospinning of the silica fibers.
43. The method of claim 25, wherein forming the anode region comprises incorporating the carbon additive onto the silica fiber mat prior to fragmentation of the silica fiber mat.
44. The method of claim 25, wherein forming the anode region comprises incorporating the carbon additive onto the silica fiber powder after fragmentation of the silica fiber mat.
45. The method of claim 25, wherein forming the cathode region comprises incorporating the lithium additive into the sol-gel prior to electrospinning of the sol-gel, whereby the silica fiber mat includes the lithium additive incorporated therein.
46. The method of claim 25, wherein forming the cathode region comprises incorporating the lithium additive onto the silica fibers during electrospinning of the silica fibers.
47. The method of claim 25, wherein forming the cathode region comprises incorporating the lithium additive onto the silica fiber mat prior to fragmentation of the silica fiber mat.
48. The method of claim 25, wherein forming the cathode region comprises incorporating the lithium additive onto the silica fiber powder after fragmentation of the silica fiber mat.
Citation Information
Patent Citations
Silica fiber composition and method of use
US10111783B1
Silica fiber compositions and methods of use
US20190255223A1
Topical compositions incorporating silica fibers
US20190269709A1
Compositions incorporating silica fibers
US20190270274A1
Method for accelerated wound healing using novel fibrous webbings
US8088965B2